Empirical Analysis of The Reality of Gender Inclusiveness of Participatory Forest Management Model: The Case Of Chilimo-Gaji Forest, West Shewa Zone, Oromia Regional State, Ethiopia - Saguye, Tesfaye Samuel (American Journal of Human Ecology, 2018)
In recognition of the continued forest deforestation, degradation and loss of biodiversity associated with the conventional “fences and fines” forest management system a new discourse has introduced since the 1990s, emphasizing the need to incorporate the aspirations of local people in forest conservation strategies in Ethiopia. The main purpose of this study was to analyze the extent of gender participation in this new forest management model in Chilimo-Gaji forest. In this study seven PFM groups were randomly selected from existing twelve PFM groups.Both qualitative and quantitative methods particularly semi-questionnaire survey, key informant interview and focus group discussion were employed to collect the data. Analysis of data revealed that PFM process in the study area was gender exclusionary in reality. Planning and decision-making activities were almost fully Forest Department (FD) and men dominated whereas implementation activities were to some extent gender inclusive. PFM groups in the study area have considerable involvement in implementation and benefit sharing of PFM activities. However, Women’s have little or no involvement in the planning and decision making of PFM process.